Organizational change as a tool for enhancing organization development. A case study of Coca-Cola bottling company limited - Stephen Donkor (KNUST, 2025)
Thesis submitted to the Department of Marketing and Corporate Strategy, Kwame Nkrumah University of Science and Technology (KNUST), in partial fulfilment of the requirement for the degree of Master of Business Administration